PERANCANGAN SISTEM INFORMASI MANAJEMEN BADAN AMAL MENGGUNAKAN METODE WATERFALL - Aidil Saputra Kirsan; Nursanti Novi Arisa; Alvian Hayyu Diansa Putra (Universitas Islam Balitar, 2022)
Developments and advances in information technology are now increasingly advanced by providing convenience for the public in accessing information in the current era of public information. The Charity Management Information System is a service application for the community to optimize donors who want to donate in an easy and fast way. The method used in designing this service application uses the Waterfall method with the Laravel Framework. The Waterfall method consists of, Requirements and Analysis, Design, Development, Testing, and Maintenance. The results obtained using this method are Entity Relationship Diagram (ERD) models and Use Case Diagrams at the Design stage. Then, at the Testing stage, an appropriate or valid status is generated from the expected results. This system or website can increase public awareness about the importance of making donations, be it Zakat, Alms, Infaq, or Waqf. And can assist in managing donation data (Zakat, Alms, Infaq, and Waqf) effectively and efficiently, namely to BMI partners (Baitulmaal Munzalan Indonesia).